2002
DOI: 10.1046/j.1444-2906.2002.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na-gluconate on the physical properties of preheated and two-step heated gel prepared from walleye pollack surimi

Abstract: Effect of Na‐gluconate on physical properties of preheated and two‐step heated gel prepared from walleye pollack surimi was investigated in connection with the progress of the cross‐linking reaction of myosin heavy chain (HC). The salt‐ground surimi to which either 8% sorbitol or Na‐gluconate was added, was preheated at 25°C or 40°C. Increases in the breaking strength and the breaking strain, together with the cross‐linking reaction of HC, of the salt‐ground surimi with Na‐gluconate proceeded more slowly than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, microbial transglutaminase enhanced breaking strength through cross‐linking of myosin by ε‐(γ‐glutamyl)lysin and resulted in the formation of harder two‐step heated gels 20 . On the contrary, salt‐ground surimi with Na‐gluconate formed less elastic gel despite the suppression of cross‐linking of myosin with covalent bonding, suggesting the involvement of modification in network formation by intermolecular bonding and/or tangling of myosin molecules by non‐covalent interactions 8 . Further, Kitakami et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, microbial transglutaminase enhanced breaking strength through cross‐linking of myosin by ε‐(γ‐glutamyl)lysin and resulted in the formation of harder two‐step heated gels 20 . On the contrary, salt‐ground surimi with Na‐gluconate formed less elastic gel despite the suppression of cross‐linking of myosin with covalent bonding, suggesting the involvement of modification in network formation by intermolecular bonding and/or tangling of myosin molecules by non‐covalent interactions 8 . Further, Kitakami et al.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous papers 7,8 demonstrated that salt‐ground surimis with Na‐gluconate formed two‐step heated gels with higher gel stiffness than those without Na‐gluconate at identical breaking strength. Thus, two‐step heated gels with Na‐gluconate were characterized as harder but less elastic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Na‐gluconate is known to have a cryoprotective effect as well as a solubilizing effect of myofibrillar protein 8,9 . Because of these characteristics, together with the weak salty taste and the healthy function to improve intestinal bacterial flora, 10,11 several studies 12–16 have been carried out on the application of Na‐gluconate to seafood processing as a substitution of NaCl and/or sugars. Na‐malate has been already applied for reduction of NaCl content in fish egg products 17 .…”
Section: Introductionmentioning
confidence: 99%